2016
DOI: 10.1186/s13059-016-1092-z
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor immune microenvironment characterization in clear cell renal cell carcinoma identifies prognostic and immunotherapeutically relevant messenger RNA signatures

Abstract: BackgroundTumor-infiltrating immune cells have been linked to prognosis and response to immunotherapy; however, the levels of distinct immune cell subsets and the signals that draw them into a tumor, such as the expression of antigen presenting machinery genes, remain poorly characterized. Here, we employ a gene expression-based computational method to profile the infiltration levels of 24 immune cell populations in 19 cancer types.ResultsWe compare cancer types using an immune infiltration score and a T cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
668
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 760 publications
(737 citation statements)
references
References 88 publications
30
668
0
1
Order By: Relevance
“…In line with this hypothesis, whole exome sequencing analysis have revealed that the loss-of-function mutation in chromatin remodeler polybromo-1 gene is a key factor causing altered immune signalling pathways in patients with metastatic ccRCC 32. Furthermore, expression of major histocompatability complex class I antigen presenting machinery could reflect the prognosis and immunotherapeutic benefits in ccRCC 31. Given the close relationship between ccRCC and immune signalling, limited evidence has illustrated the function and clinical significance immune checkpoint HHLA2 in ccRCC pathogenesis and prognosis.…”
Section: Introductionmentioning
confidence: 91%
“…In line with this hypothesis, whole exome sequencing analysis have revealed that the loss-of-function mutation in chromatin remodeler polybromo-1 gene is a key factor causing altered immune signalling pathways in patients with metastatic ccRCC 32. Furthermore, expression of major histocompatability complex class I antigen presenting machinery could reflect the prognosis and immunotherapeutic benefits in ccRCC 31. Given the close relationship between ccRCC and immune signalling, limited evidence has illustrated the function and clinical significance immune checkpoint HHLA2 in ccRCC pathogenesis and prognosis.…”
Section: Introductionmentioning
confidence: 91%
“…Melanoma and NSCLC typically harbor 10 to 400 mutations per megabase (Mb) and these genetic variants can generate tumor-specific antigens (neoantigens) that stimulate a strong anti-tumor immune response (14). In contrast, ccRCC harbors an average of only 1.1 mutations/Mb (6, 7) yet it ranks highly among tumor types in terms of immune cytolytic activity (8), immune infiltration score, and T cell infiltration score in the tumor microenvironment (9). These observations led us to hypothesize that distinct molecular mechanisms underlie the immunologically active tumor microenvironment and responsiveness to immune checkpoint therapy in patients with ccRCC.…”
mentioning
confidence: 99%
“…However, the magnitudes of these differences were small and potentially confounded by differing degrees of tumor-stromal admixture (fig. S7, A to C) (9). We also examined LOF mutations in VHL , the most commonly-mutated gene in the TCGA ccRCC cohort.…”
mentioning
confidence: 99%
“…We explored correlation between total gene fusions, predicted MHC class I binding CASQ epitopes, and immunological parameters using recently published estimates that predicted immune-cell infiltrates using RNA-sequencing data [37]. For immune cell-infiltrates, we used published infiltration estimates for the patients included in this cohort generated, estimated via a single sample gene set enrichment analysis (ssGSEA) approach performed across multiple cancers [37].…”
Section: Methodsmentioning
confidence: 99%